PENGARUH HARGA IPO, PORSI SAHAM, DAN RASIO WARAN TERHADAP CAPITAL GAIN PADA PASAR PERDANA DI BURSA EFEK INDONESIA - Sunarso Sunarso; M. As'ari (Sekolah Tinggi Ilmu Ekonimi IPWI Jakarta, 2017)
This paper is presented to reveal the corelation of IPO Portion and Warrant Ratio to the Capital Gain at Indonesian Stock Exchange (IDX) in the first day listin. Usually, most of stocks that are contain warrants commonly give significant capital gain. If the stocks price rise the investors get double or even triple profit, from the stocks and from the warrants. If the stocks price fall, the investors still get profit from the warrants. The companies give warrants in the IPO is aimed to give incentive to the investors so than the stocks are absorved by the initial public offering. That is why usually the IPO oversubscribed more than twice. The problem is what is the correlation between IPO portion and Warrant Ratio to the Capital Gain? To get the answer this research is held. The research menthod in this paper is a quatitative analitical reseach base on secondary data sources. The data taken from IDX market information concerning IPO followed by warrants in the last three years. The facts that are found in this research are: 1 IPO price, shares portion, and warrant ratio are negatively correlated with capital gain in the first listing day.2. All the new comers with warrants bonus gave significant capital gain. 3. All independent variables give negative impact to the dependent variable. Key words: IPO, Waran, Pasar Perdana, Capital Gain